De facto unions in private international law - Dougan, Filip (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2023)
Over the past few decades, there has been a discernible trend among the European Union (EU) member states to regulate various aspects of de facto unions. Nonetheless, comparative analyses still reveal significant divergences in domestic laws. Within this spectrum, one may observe legal systems in which no explicit rules are envisaged for de facto unions, juxtaposed with those wherein the legal effects of such unions converge to- wards those of marriage. These differences in domestic substantive regulations of de facto unions inevitably pose formidable challenges for private international law. The article attempts to scrutinise the legal position of de facto unions under EU private international law and assess the extent to which such unions may benefit from the existing legal instru- ments. Overall, great fragmentation may be observed in the approaches found across var- ious EU Regulations. In the second part, the article focuses on the regulatory landscape of de facto unions in Slovenia, encompassing both substantive and private international law aspects. Although Slovenia was once at the forefront of regulating de facto unions, it is now evident that the existing regulation in private international law is outdated and necessitates reform. This is particularly important, given that Slovenian substantive law attaches significant legal consequences to de facto unions, and such unions have become increasingly prevalent within Slovenian society.
Keywords: Evropska unija; mednarodno zasebno pravo; pravna ureditev; zakonodaja; zunajzakonska skupnost